SELF MONITORING PEREMPUAN YANG BERCERAI DALAM PENYESUAIAN DIRI DI LINGKUNGAN - Nur’aeni Nur’aeni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2011)
The purpose of this research was to acquire image about the divorced female self-monitoring in self-adaptation of her sphere. This research used method by descriptive case study with qualitative approach. To get data was used indepth interview. Analyse data in this research applying for interactive analyzing model with three steps, presentation, reduction, and verification data. The research located in Purwokerto. The research informant was determined intentionally building on various judgement. There was 6 primary informants and 6 secondary informnat in this research. The result of this research shows cause of divorced female is husband propose to wife cease from work, dishonest husband, wife suffer materially and spiritually, husband is not worked, husband blackmail money’s wife, and household violence. Informants feeling after divorce were happiness, disappointed because they felt not gulty to her husband, more quiet and roomy. Most large of the female divorced could self-adapt in her sphere, despite of there were two informants feel no self-adaptation. Keywords: self-monitoring, female divorced